Digital Newsroom Transformation: A Systematic Review of the Impact of Artificial Intelligence on Journalistic Practices, News Narratives, and Ethical Challenges - Alem Febri Sonni; Hasdiyanto Hafied; Irwanto Irwanto; Rido Latuheru (Journalism and Media)
Artificial Intelligence (AI) fundamentally changes journalism, yet a comprehensive understanding of its impact is limited. This study presents the first systematic review to thoroughly analyze the influence of AI on journalistic practices, news narratives, and emerging ethical challenges. A rigorous analysis of 127 studies selected from 2478 original articles reveals trends in AI adoption in newsrooms, changes in journalists’ roles, innovations in news presentation, and emerging ethical implications. The key findings show a significant increase in the use of AI for news writing automation (73% of news organizations), data analysis (68%), and content personalization (62%). While AI improves efficiency and accuracy, 42% of studies reported concerns about reduced levels of nuance and context in AI-generated news. We also identified the emergence of hybrid “journalist–programmer” roles (52% of studies) and the need for “AI literacy” among journalists (38% of studies). The most prominent ethical challenges include algorithm transparency (82% of studies), data privacy (76%), and accountability relative to AI content (71%). Regional analysis reveals significant gaps in AI adoption, with important implications for global information equity. This review highlights the ongoing transformation in journalism, identifies critical gaps in current research, and offers an agenda for future investigation. Our findings provide valuable insights for media practitioners, policymakers, and researchers seeking to understand and shape the future of journalism in the age of AI.